2017
DOI: 10.1111/bph.13773
|View full text |Cite
|
Sign up to set email alerts
|

Signalling mechanisms underlying doxorubicin and Nox2 NADPH oxidase‐induced cardiomyopathy: involvement of mitofusin‐2

Abstract: Background and PurposeThe anthracycline doxorubicin (DOX), although successful as a first‐line cancer treatment, induces cardiotoxicity linked with increased production of myocardial ROS, with Nox2 NADPH oxidase‐derived superoxide reported to play a key role. The aim of this study was to identify novel mechanisms underlying development of cardiac remodelling/dysfunction further to DOX‐stimulated Nox2 activation.Experimental ApproachNox2−/− and wild‐type (WT) littermate mice were administered DOX (12 mg·kg−1 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 78 publications
5
26
0
Order By: Relevance
“…Cardiac tissue is especially vulnerable to free radicals induced by DOX because the hearts had a lot of mitochondria and cardiac antioxidant enzymes were relatively lower compared with other organs [10]. Previous studies have shown that increased levels of cardiac reactive oxygen species (ROS) were observed during the development of DOX-induced cardiomyopathy [11]. Excessive ROS accumulation caused lipid peroxidation, structural changes of biological macromolecules, and eventually result in cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac tissue is especially vulnerable to free radicals induced by DOX because the hearts had a lot of mitochondria and cardiac antioxidant enzymes were relatively lower compared with other organs [10]. Previous studies have shown that increased levels of cardiac reactive oxygen species (ROS) were observed during the development of DOX-induced cardiomyopathy [11]. Excessive ROS accumulation caused lipid peroxidation, structural changes of biological macromolecules, and eventually result in cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…DOX-induced cardiomyocyte apoptosis and atrophy, interstitial fibrosis, leukocyte infiltration, and cardiac dysfunction in wild-type (WT) mice were attenuated in Nox2 −/− mice [33,39]. DOX-induced superoxide production was also mitigated in this animal model [39].…”
Section: Oxidative Stressmentioning
confidence: 86%
“…An in vitro study using NADPH oxidase inhibitors (diphenyliodonium and apocynin) on H9c2 cells showed that DOX-induced apoptosis was mitigated, demonstrating NADPH oxidase is also involved in the development of cardiac toxicity induced by DOX [36]. Furthermore, there is accumulating evidence to support an important role for Nox2 NADPH oxidase (one of the seven different NADPH oxidase isoforms) in DIC, identified using Nox2-deficient (Nox2 −/− ) or gp91phox knock-out (gp91 −/− ) mice [33,[37][38][39]. DOX-induced cardiomyocyte apoptosis and atrophy, interstitial fibrosis, leukocyte infiltration, and cardiac dysfunction in wild-type (WT) mice were attenuated in Nox2 −/− mice [33,39].…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The anthracycline agent, doxorubicin, is commonly used to treat a diverse range of cancers and is notorious for associated risk of cardiomyopathy, which may largely be mediated by oxidative stress. To specifically investigate the role of the NADPH oxidase NOX2, previously implicated in doxorubicin-induced cardiotoxicity (Zhao et al, 2010), McLaughlin et al (2017) performed microarray analysis of left ventricular tissue from doxorubicin-treated Nox2 À/À and wild-type mice, which highlighted the particular involvement of cell death and survival pathways. They specifically focussed on mitofusin-2 (Mfn2), a mitochondrialshaping protein that has been implicated in cardiomyocyte health and survival (Ong et al, 2017), and reported that activation of Mfn2 signalling appears to be protective against doxorubicin cardiotoxicity.…”
Section: London Ukmentioning
confidence: 99%